In-Vitro Assessment of Artificial Tooth Material Wear Behavior Using 3D Wear Analysis - Sıla Yelekçi; Ayben Şentürk; Funda Akaltan (Journal of Functional Biomaterials, 2025)
Background: Artificial tooth wear impacts prosthesis durability and function; understanding material–antagonist interactions guides clinical choices. Aim: This in-vitro study aimed to assess the wear behavior of isosit and nanohybrid composite resin artificial teeth when opposed to various antagonist materials using 3D volumetric wear analysis. Materials and Methods: Sixty specimens (n = 10 per group) were prepared from two artificial tooth materials and assigned to six antagonist combinations: isosit–isosit, isosit–nanohybrid composite, isosit–porcelain, nanohybrid composite–isosit, nanohybrid composite–nanohybrid composite, and nanohybrid composite–porcelain. Specimens were scanned before and after 600,000 chewing cycles using a structured-light 3D scanner. Volumetric wear was calculated by superimposing pre- and post-test scans. Data were analyzed using two-way ANOVA and Tukey’s HSD test (α = 0.05). Results: Porcelain antagonists produced the highest wear values (p < 0.05). No significant difference was found between isosit and nanohybrid antagonists (p > 0.05). Identical material pairings showed less wear, though differences were not statistically significant. Conclusions: Porcelain as an antagonist increased wear risk. Using identical materials bilaterally, such as isosit–isosit or nanohybrid–nanohybrid, may help reduce artificial tooth wear in removable prostheses.